Capabilities of Baltic Sea models to assess environmental status for marine biodiversity. (August 2016) - Tedesco, Letizia; Piroddi, Chiara; Kämäri, Maria; Lynam, Christopher
Abstract: To date there has been no evaluation of the capabilities of the Baltic Sea ecosystem models to provide information as outlined by the Marine Strategy Framework Directive. This work aims to fill in this knowledge gap by exploring the modelling potential of nine Baltic Sea ecosystem models to support this specific European policy and, in particular, models' capabilities to inform on marine biodiversity. Several links are found between the Model-Derived Indicators and some of the relevant biodiversity-related descriptors (i.e. biological diversity and food webs), and pressures (i.e. interference with hydrological processes, nutrient and organic matter enrichment and marine acidification). However several gaps remain, in particular in the limited representation of habitats other than the pelagic that the models are able to address for descriptor sea-floor integrity and inability to assess descriptor non-indigenous species. The general outcome is that the Baltic Sea models considered do not adequately cover all the requested needs of the MSFD, but can potentially do so to a certain extent, while for some descriptors/criteria/indicators/pressures new indicators and/or modelling techniques need to be developed in order to satisfactorily address the requirement of the MSFD and assess the environmental status of the Baltic Sea.